Comparison of Maternal Outcomes between Clinical and Subclinical Hypothyroid Pregnant Women admitted in a Subspecialty Department of a Tertiary Hospital - Sharmin, Farzana; Asma, Mahfuja; Mahmud, Sanzida; Momin, Afzal; Das, Tripti Rani; Begum, Firoza (Journal of Current and Advance Medical Research, 2021)
Background: Women with Hypothyroidism have higher pregnancy complication rates. Objective: The purpose of the present study was to compare the effects of clinical and subclinical hypothyroidism on maternal outcomes. Methodology: This cohort study was conducted in the Feto-Maternal Department of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from a period of 6 months dated from September 2019 to February 2020 for a period of 6 months. All cases of the clinical and sub-clinical hypothyroid pregnant women admitted in this department. Maternal outcomes of both groups during pregnancy were recorded. Findings of the cases recorded carefully. Result: This study was conducted among 75 patients, which was 14.79% of the total admitted cases during study period. Maximum (62.79%) number was found in the age group of 25 to 44 years in group I and 65.62% cases in group II. (p<0.05). Severe Pre Eclampsia was observed 2(4.65%) cases and 6(18.75%) Group II. Abruptio placenta was observed 5(15.62%) cases in group II and none in group I. However Preterm delivery are three times more 39.5% in group I cases. Uterine rupture, abortion are observed only in group II patients (p<0.05). Conclusion: In conclusion maternal outcomes are significantly varied in clinical and subclinical hypothyroidism women during pregnancy. Journal of Current and Advance Medical Research, January 2021;8(1):7-11